Tearing mode stabilization by electron cyclotron resonant heating in EAST tokamak experiments. (12th August 2021) - Zhang, Y.; Wang, X.J.; Zhang, X.D.; Xu, H.D.; Gu, S.; Zhou, T.F.; Shi, T.H.; Liu, H.Q.; Wang, X.J.; Wang, H.H.; Zang, Q.; Luo, Z.P.; et al.
Abstract: Tearing mode stabilization by electron cyclotron waves (ECWs) has been carried out in Experimental advanced superconductiong tokamak (EAST) experiments. The effects of the amount of ECW power and the radial wave deposition location on stabilizing the m / n = 2/1 magnetic island are investigated, where m / n is the poloidal/toroidal mode number. The local heating is found to dominate the mode stabilization in these experiments. The stabilization is more effective when the wave is deposited closer to the radial island location, as expected. With increasing ECW power, however, the tearing modes are not stabilized completely, and the island width saturates at a finite width. Moreover, the island rotation frequency is found to decrease when the ECW deposition is close to the island such that the island width is reduced significantly. Using externally applied, rotating resonant magnetic perturbations to generate slowly rotating magnetic islands, the locked island stabilization by ECW has also been studied, and the island width reduction and nonuniform island rotation are observed when the island's center passes through the ECW deposition region.